Contribuição da imagem tomográfica na avaliação de lesões ósseas da região bucomaxilofacial - Tomeh, Jorge Elias Kaluf (2015)
Computed tomography (CT) is a resource used in both for the diagnosis and the treatment of maxilomandibular bone lesions. The rational use of this imaging method should be guided by specific studies that reveal its real contribution and indication in the conduct of bone lesions. Objective - It is proposed to analyze the role of CT in the assessment of bone lesions in the maxillofacial region. Metodology - The sample consisted of patients with any type of bone lesion, whose diagnosis had already been made on the basis of anatomopathological findings and for whom the use of panoramic radiograph (PR) and CT was required. The examinations were performed by two radiology specialists and two maxillofacial surgeons. The criteria used were: internal arrangement, limits and changes on the surrounding anatomical structures. In addition, the examiners suggested a possible diagnosis at the end of analysis. Results - Low to moderate concordance was found. In 61,5% of cases, the possible diagnoses made after CT analysis agreed with the anatomopathological results. Conclusion - The CT has the potential to add new information to the patient's treatment plan and, when properly indicated, to contribute for the evaluation of maxillofacial bone lesions.